2017
DOI: 10.1371/journal.pone.0174060
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of sortase SrtA2 to Lactobacillus casei BL23 inhibition of Staphylococcus aureus internalization into bovine mammary epithelial cells

Abstract: Probiotics have been considered as a promising strategy to prevent various diseases in both humans and animals. This approach has gained interest in recent years as a potential means to control bovine mastitis. In a previous study, we found that several L. casei strains, including BL23, were able to inhibit the internalization of S. aureus, a major etiologic agent of mastitis, into bovine mammary epithelial cells (bMEC). This antagonism required a direct contact between L. casei and bMEC or S. aureus, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The proportion of cells with fluorescence labeling of H2 and NZ2114 were reduced by 13.9% and 3.4%, respectively, and the fluorescence intensity of the cells decreased sharply (Fig. 4C,D), indicating that low temperature may have an inhibitory effect on peptide uptake 28 . In the inhibitor-treated groups, the fluorescence intensity of the cells treated with chlorpromazine (an inhibitor of clathrin-mediated endocytosis) decreased sharply; however, the fluorescence intensity did not change following treatment with amiloride (an inhibitor of macropinocytosis), methyl-β-cyclodextrin (MβCD) (a disruptor of lipid rafts), and nocodazole (an inhibitor of microtubule polymerization) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The proportion of cells with fluorescence labeling of H2 and NZ2114 were reduced by 13.9% and 3.4%, respectively, and the fluorescence intensity of the cells decreased sharply (Fig. 4C,D), indicating that low temperature may have an inhibitory effect on peptide uptake 28 . In the inhibitor-treated groups, the fluorescence intensity of the cells treated with chlorpromazine (an inhibitor of clathrin-mediated endocytosis) decreased sharply; however, the fluorescence intensity did not change following treatment with amiloride (an inhibitor of macropinocytosis), methyl-β-cyclodextrin (MβCD) (a disruptor of lipid rafts), and nocodazole (an inhibitor of microtubule polymerization) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Also, EVs from probiotic bacteria have comparable effects to whole bacteria, increasing the number of T reg cells, in case of L. rhamnosus JB-1 9 , and promoting the survival of Caenorhabditis elegans exposed to vancomycin-resistant E. faecium by L. plantarum WCFS1 10 . Analysis of EVs from probiotic lactobacilli, like Lactobacillus rhamnosus , L. plantarum , L. reuteri and L. casei , showed that they contained glycolytic enzymes, chaperonins 9 , 11 14 and ligase functions 15 . In addition to proteins and membrane phospholipids, EVs from Gram-positive bacteria also contain lipoteichoic acid (LTA).…”
Section: Introductionmentioning
confidence: 99%
“…Various cell surface components, such as proteins, peptidoglycans, teichoic acids and polysaccharides contribute to the interaction of LAB with epithelial cells (Piqué et al, 2019;Taverniti and Guglielmetti, 2011). A L. casei BL23 srtA2 mutant, srtA2 encoding a sortase, was less effective in inhibiting S. aureus adhesion to and internalisation into bMECs (Souza et al, 2017). This characteristic was associated with an altered abundance of LPXTG and moonlighting proteins at the surface of the srtA2 mutant strain as well as with modifications of the cell wall structure.…”
Section: Heat-inactivated Lactobacillus Gasseri La806 Retains Beneficmentioning
confidence: 99%